2016
DOI: 10.1142/s0219633616500061
|View full text |Cite
|
Sign up to set email alerts
|

Ab-initio HF and density functional theory investigations on the synthesis mechanism, conformational stability, molecular structure and UV spectrum of N’-Formylkynurenine

Abstract: Tryptophan methyl ester (Trp-ME) degrades with singlet oxygen and produce compounds which are photosensitizers and may react to form other derivatives such as N’-Formylkynurénine (NFK) and kynurenine, which are the final products of this oxidation. In order to study and optimize the molecular structure of NFK and determine its different thermodynamic properties, we performed a conformational analysis by DFT/B3LYP method with 3-21G basis set. Six most stable conformations were observed through the analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The frontier orbital energies, such as the highest occupied molecular orbital energy (HOMO), lowest unoccupied molecular orbital (LUMO) and band gaps, are critical parameters for kinetic and thermodynamic stability studies, and prediction of reactivity and photochemical properties. 41 , 42 , 43 , 44 , 45 , 46 The frontier orbital molecular overlay revealed that the HOMO overlay was essentially on ring, extending over the two nitrogen atoms of the pyrazole ring, whereas the LUMO overlay was on the phenyl ring for M1, M3, M4 and M5 , and was on the benzoyl ring for M1 and M6 ( Figure 1 ). The calculated frontier molecular orbitals LUMO, HOMO and HOMO–LUMO (ΔEg) were, respectively, −2.50, −5.92 and 3.42 eV for M1 ; −2.77, −5.91 and 3.14 eV for M2 ; −2.85, −5.87 and 3.02 eV for M3 ; −2.43, −5.86 and 3.43 eV for M4 ; −2.42, −5.86 and 3.37 eV for M5 ; −2.90, −6.06 and 3.16 eV for M6 ; and −2.26, −6.10 and 3.83 for Ma .…”
Section: Resultsmentioning
confidence: 99%
“…The frontier orbital energies, such as the highest occupied molecular orbital energy (HOMO), lowest unoccupied molecular orbital (LUMO) and band gaps, are critical parameters for kinetic and thermodynamic stability studies, and prediction of reactivity and photochemical properties. 41 , 42 , 43 , 44 , 45 , 46 The frontier orbital molecular overlay revealed that the HOMO overlay was essentially on ring, extending over the two nitrogen atoms of the pyrazole ring, whereas the LUMO overlay was on the phenyl ring for M1, M3, M4 and M5 , and was on the benzoyl ring for M1 and M6 ( Figure 1 ). The calculated frontier molecular orbitals LUMO, HOMO and HOMO–LUMO (ΔEg) were, respectively, −2.50, −5.92 and 3.42 eV for M1 ; −2.77, −5.91 and 3.14 eV for M2 ; −2.85, −5.87 and 3.02 eV for M3 ; −2.43, −5.86 and 3.43 eV for M4 ; −2.42, −5.86 and 3.37 eV for M5 ; −2.90, −6.06 and 3.16 eV for M6 ; and −2.26, −6.10 and 3.83 for Ma .…”
Section: Resultsmentioning
confidence: 99%
“…Sharma et al emphasized that the smallest band gap and the negativity indicated the increasing activity of the compounds to inhibit HIV. Omri et al emphasized that identifying the most stable conformation of the molecule by analyzing thermodynamic, electronic and orbital properties by the theoretical study using HF and DFT/B3LYP with 6‐31G(d,p) basis sets were important methods.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al [27] emphasized that the smallest band gap and the negativity indicated the increasing activity of the compounds to inhibit HIV. Omri et al [28] emphasized that identifying the most stable conformation of the molecule by analyzing thermodynamic, electronic and orbital properties by the The important substances against hydroxyl radicals come from the antioxidants. Antioxidants have reducing power to the radical agents; they take part in redox reactions by donating electrons or hydrogen atoms.…”
Section: Discussionmentioning
confidence: 99%
“…While the energy of HOMO is directly related to ionization potential and LUMO energy is to electron affinity. Recently, the energy gap between HOMO and LUMO has been used to confirm the bioactivity from ICT [Omri et al 2016; Kosar et al 2011]. The atomic orbital compositions of the frontier molecular orbitals are shown in Fig.…”
Section: Analysis Of Frontier Molecular Orbitalsmentioning
confidence: 99%